1999
DOI: 10.1021/jp9832950
|View full text |Cite
|
Sign up to set email alerts
|

Programming a Gold Nanocrystal to Recognize and Selectively Bind a Molecular Substrate in Solution

Abstract: Gold nanocrystals stabilized by a chemisorbed mixture of a long-chain alkane thiol, namely dodecanethiol (95%), and a long-chain dodecanethiol incorporating a receptor, namely 12-mercaptododecyl-1-uracil (5%), have been prepared. In solution, these nanocrystals recognize and selectively bind a long-chain alkane incorporating a complementary substrate, namely, N, N′-2,6-pyridinediylbis[undecamide].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
1
21
1
Order By: Relevance
“…The stable dispersion of dodecanethiol-modified AuNPs was prepared by the method described by Brust et al [44] The nearly size-monodisperse fraction was subsequently modified by the exchange of the adsorbed thiol for thiol-incorporating crown molecules (dodecanethiol incorporating a crown moiety in the terminal position). [61] The MWNTs were modified by two amide-coupling reactions: the first was between the carboxy-modified MWNTs and ethylenediamine, and the second between the remaining amine of the coupled ethylenediamine and the cation precursor [N-(4-carboxydibenzylamine)carbamate]. For the templated self-assembly of a gold nanowire in solution, a dispersion of crown-modified AuNPs in chloroform was added to a freshly sonicated suspension of cation-modified MWNTs in chloroform.…”
Section: Preparation Of Aunp-filled Cntsmentioning
confidence: 99%
“…The stable dispersion of dodecanethiol-modified AuNPs was prepared by the method described by Brust et al [44] The nearly size-monodisperse fraction was subsequently modified by the exchange of the adsorbed thiol for thiol-incorporating crown molecules (dodecanethiol incorporating a crown moiety in the terminal position). [61] The MWNTs were modified by two amide-coupling reactions: the first was between the carboxy-modified MWNTs and ethylenediamine, and the second between the remaining amine of the coupled ethylenediamine and the cation precursor [N-(4-carboxydibenzylamine)carbamate]. For the templated self-assembly of a gold nanowire in solution, a dispersion of crown-modified AuNPs in chloroform was added to a freshly sonicated suspension of cation-modified MWNTs in chloroform.…”
Section: Preparation Of Aunp-filled Cntsmentioning
confidence: 99%
“…Crown ethers, for instance, have been shown to be excellent receptors for ammonium ions forming inclusion complexes. [19] To integrate this motif into nanoparticle systems, the groups of Fitzmaurice and Stoddart have synthesized gold MPCs featuring dibenzo [24]crown-8 ether moieties on the surface. [20] Through NMR experiments it has been shown that these MPCs in fact form pseudorotaxanes on the surface by binding dibenzylammonium ions to an 86 % coverage ( Figure 5).…”
Section: Molecular Recognition Using Nanoparticlesmentioning
confidence: 99%
“…[21] In these studies silver nanoparticles featuring dilute (15 %) dibenzo [24]crown-8 groups embedded in a dodecanethiol monolayer were synthesized through placeexchange reactions. Addition of stoichiometric amount of a ditopic bis-ammonium salt led, as expected, to a slow formation of a larger aggregates composed of individual MMPCs linked through [3]pseudorotaxane complexes ( Figure 6).…”
Section: Molecular Recognition Using Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations